The Role of Political Skill in Interaction of Psychological Contract Breach to Counterproductive Work Behavior - Andi Tenri Pada; Gugup Kismono (Kusuma Negara Business School, 2020)
This study discusses psychological contract breach and specifically focuses on joint moderating roles of political skill of employees to explain the formation of counterproductive work behavior. The mechanism explains by Social Exchange Theory (Blau,1964) and Conservation Resources Theory (Hobfoll,1989). As predicted, we found that psychological contract breach lead to counterproductive work behavior. Moreover, the study indicate that political skill is a moderator and plays a role in social exchange relationship quality for psychological contract breach and counterproductive work behavior. The result showed that high political skill led to the weakest relationship between psychological contract breach and counterproductive work behavior (i,e., CWB-O and CWB-I). This study was conducted by doing a survey on private and public sectors in Indonesia and employed 260 supervisors as samples. Discussion about finding in this study along with theoretical and practical implications are presented completely.